Handbook on Accounting, Statistics. and Business Office Procedures for Hospitals (Book). - Allyn, Robert G. (The Accounting Review, 1952)
Reviews the book "Handbook on Accounting, Statistics and Business Office Procedures for Hospitals: Uniform Hospital Statistics and Classification of Accounts."